2023
DOI: 10.1039/d3nr00999h
|View full text |Cite
|
Sign up to set email alerts
|

Inside a nanocrystal-based photodiode using photoemission microscopy

Abstract: As nanocrystal-based devices gain maturity, a comprehensive understanding of their electronic structure is necessary for further optimization. Most spectroscopic techniques typically examine pristine materials and disregard the coupling of the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…As a result, it was not well-suited for conventional vertical geometry diodes, which led us to focus on a planar version of the junction. 39 The fabrication procedure for the planar junction is outlined in Figure S27. Briefly, a Si/SiO 2 wafer was initially covered with a gold layer to minimize sample charging.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, it was not well-suited for conventional vertical geometry diodes, which led us to focus on a planar version of the junction. 39 The fabrication procedure for the planar junction is outlined in Figure S27. Briefly, a Si/SiO 2 wafer was initially covered with a gold layer to minimize sample charging.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Second, the method, relying on soft X-rays, had a very limited photoelectron escape depth (few nm), which meant that it could only probe the sample’s surface. As a result, it was not well-suited for conventional vertical geometry diodes, which led us to focus on a planar version of the junction . The fabrication procedure for the planar junction is outlined in Figure S27.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Cavallo et al have reported the use of such a method to probe the scalar energy landscape of NC-based field-effect transistors 20,21 and a photodiode. 22 In particular, the method has been insightful in probing surface band bending at the NC semiconductor−electrode interface 20 by providing direct evidence of the gate bias effect on the band alignment and unveiling the built-in potential of a diode. 22 In this report, we explore how photoemission microscopy can be used to probe the vectorial electric field distribution in a FPA-like structure under operation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…22 In particular, the method has been insightful in probing surface band bending at the NC semiconductor−electrode interface 20 by providing direct evidence of the gate bias effect on the band alignment and unveiling the built-in potential of a diode. 22 In this report, we explore how photoemission microscopy can be used to probe the vectorial electric field distribution in a FPA-like structure under operation. Such output will be critical for the future modeling of complex devices such as infrared imagers.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation